2018
DOI: 10.1140/epjc/s10052-018-5965-z
|View full text |Cite
|
Sign up to set email alerts
|

Does particle creation mechanism favour formation of black hole or naked singularity?

Abstract: The paper deals with collapse dynamics of a spherically symmetric massive star in the framework of non-equilibrium thermodynamic prescription through particle creation mechanism. The matter content in the star is in the form of perfect fluid with barotropic equation of state, and the dissipative phenomena due to non-equilibrium thermodynamics is in the form of bulk viscosity. For simplicity, the thermodynamic system is chosen to be adiabatic so that the effective bulk viscous pressure is linearly related to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…In the BH scenario, the apparent horizon forms at a stage earlier than the singularity formation. The outside event horizon then entirely covers the final stages of collapse when the singularity forms, while the apparent horizon inside the matter evolves from the outer shell to reach the singularity at the instant of its formation [61,62]. The equations (32) and (33) show that t AH and t s both give finite time durations.…”
Section: Occurrence Of Black Holementioning
confidence: 99%
“…In the BH scenario, the apparent horizon forms at a stage earlier than the singularity formation. The outside event horizon then entirely covers the final stages of collapse when the singularity forms, while the apparent horizon inside the matter evolves from the outer shell to reach the singularity at the instant of its formation [61,62]. The equations (32) and (33) show that t AH and t s both give finite time durations.…”
Section: Occurrence Of Black Holementioning
confidence: 99%
“…Using the WKB approach, the number density and renormalized energy-momentum tensor of the created spin-1/2 particle in the spatially flat (3+1)-dimensional Friedmann-Robertson-Walker (FRW) spacetime have been calculated [20]. The effect of the scalar particle creation on the collapse of a spherically symmetric massive star was investigated and it was demonstrated that the collapsing process was not independent from the particle creation rate [21]. Moreover, in [22] thermodynamics laws and equilibrium conditions are discussed in the presence of particle creation in the context of the (3+1)-dimensional Chern-Simons gravity theory.…”
Section: Introductionmentioning
confidence: 99%